Organelle Visualization With Multicolored Fluorescent Markers in Bamboo - Zhang, Mengdi; Hu, Shuai; Yi, Fang; Gao, Yanli; Zhu, Dongmei; Wang, Yizhu; Cai, Yi; Hou, Dan; Lin, Xinchun; Shen, Jinbo (Frontiers in Plant Science, 2021)
Bamboo is an important model plant to study the molecular mechanisms of rapid shoot growth and flowering once in a lifetime. However, bamboo research about protein functional characterization is largely lagged behind, mainly due to the lack of gene transformation platforms. In this study, a protoplasts transient gene expression system in moso bamboo has been firstly established. Using this reliable and efficient system, we have generated a set of multicolored fluorescent markers based on the targeting sequences from endogenous proteins, which have been validated by their comparative localization with Arabidopsis organelle markers, in a combination with pharmaceutical treatments. Moreover, we further demonstrated the power of this multicolor marker set for rapid, combinatorial analysis of the subcellular localization of uncharacterized proteins, which may play potential functions in moso bamboo flowering and shoot fast growth. Finally, this protoplasts transient gene expression system has been elucidated for functional analysis in protein-protein interaction by fluorescence resonance energy transfer (FRET) and co-immunoprecipitation analysis. Taken together, in combination with the set of moso bamboo organelle markers, the protoplasts transient genes expression system could be used for subcellular localization and functional study of unknown protein in bamboo and will definitely promote rapid progress in diverse areas of research in bamboo plants.